AN ANALYSIS ON SUPPLY CHAIN CHANNEL OF SWEET CORN (Zea mays) IN THE SETYO PRATOLO 2 FARMER GROUP, LINGGASARI VILLAGE, KEMBARAN SUB-DISTRICT, BANYUMAS REGENCY - Trianita Safitri; Pujiati Utami; Dumasari; Watemin (Universitas Muhammadiyah Makassar, 2026)
Sweet corn is a horticultural crop with considerable economic value and steadily increasing demand over time. However, its supply chain distribution process continues to face several challenges, particularly high marketing costs, lengthy distribution channels, and the relatively weak bargaining position of farmers. This study aims to analyze supply chain channels and measure the marketing efficiency of sweet corn within the Setyo Pratolo 2 Farmer Group located in Linggasari Village, Kembaran Sub-District, Banyumas Regency. This study employed a descriptive method with both quantitative and qualitative approaches. Data were collected through interviews, questionnaires, and documentation involving 20 farmers, 2 collectors, and 10 retailers selected using purposive sampling. Data analysis was conducted by calculating marketing margins, marketing efficiency, and farmers share to evaluate the performance of each distribution channel. The findings identified two supply chain channel patterns. Channel I (farmer-collector-consumer) and Channel II (farmer-collector-retailer-consumer). The marketing margin in Channel I was IDR 2,382/kg, which is lower than Channel II at IDR 5,334/kg. In terms of efficiency, Channel I demonstrated a marketing efficiency of 3.6%, indicating an efficient channel, whereas Channel II showed 18.5%, categorized as less efficient. Additionally, the farmers share in Channel I reached 56.7%, significantly higher than Channel II at 33.3%. Therefore, Channel I is considered the most efficient distribution channel due to its shorter distribution chain, lower marketing costs, and higher price share received by farmers.